Ten tiny babies by - Katz, Karen (Classic Board Books, 2011)
1 tiny baby starts to run. Along comes another... ...to have some fun! 2 silly babies spin around. Along comes another... ...and she falls down. The fun continues until ten tiny babies are exhausted from the day, fast asleep in their beds! Karen Katz's bright colors and irresistibly adorable babies are sure to be a hit among the learning-to-count crowd. This board book is perfect for even the youngest of readers.